METODE WANITA KARIER DALAM MEMBENTUK KELUARGA SAKINAH DI DESA BONTONGAN KECAMATAN BARAKA KABUPATEN ENREKANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
The main problem in this research is "How do career women form a harmonious family in Bontongan Village, Baraka District, Enrekang Regency?" with the following research questions:1) What are the efforts of career women in forming a harmonious family in Bontongan Village, Baraka District, and Enrekang Regency? 2) What are the results of the efforts of career women in forming a harmonious family in Bontongan Village, Baraka District, and Enrekang Regency? This research uses a descriptive qualitative research type located in Bontongan Village, Baraka District, and Enrekang Regency, with a harmonious family guidance approach. The data collection methods used are observation, interviews, and documentation. Data analysis is conducted in three stages: data reduction, data presentation, and conclusion drawing. The results of this research show that the efforts of career women in forming a harmonious family in Bontongan Village, Baraka District, and Enrekang Regency are 1) increasing faith in the household. 2) Managing time well. 3) Maintaining communication among family members. 4) Creating comfort in the home. 5) Loving and being open with each other. 6) Being responsible towards family. The results of the efforts of career women in forming a harmonious family in Bontongan Village, Baraka District, Enrekang Regency are: 1) The formation of an Islamic family. 2) The creation of a harmonious family. 3) The creation of a family full of love and affection. 4) The creation of a prosperous family. The implications of this research are: 1) Career women need to understand that their role as working women and homemakers in forming a harmonious family is very important. 2) Religious counselors need to work with the Head of Bontongan Village to improve guidance programs for harmonious families. Religious counselors also need to develop strategies or methods in forming harmonious families to increase community knowledge about harmonious families. 3) The community needs to support career women in forming harmonious families.